The Utilization of Extended Reality to Facilitate Quality Education and Reduce Inequalities - Wang, Xining (Trinity College Dublin. School of Education. Discipline of Education, 2024)
Educational inequalities pose a significant global challenge, as they hinder sustainable development and perpetuate disparities in opportunities and outcomes for different populations. To address this dilemma and offer potential solutions, this Ph.D. project pilots practices of utilizing extended reality to facilitate quality education and reduce inequities. The core research questions (RQ) of this Ph.D. project are: RQ1 Can virtual reality improve rural children's social competence and perceived social support? RQ2 Can virtual reality facilitate quality education by improving the classroom atmosphere? And RQ3 What are rural educators' perspectives on utilizing extended reality enhanced teaching and learning? To answer these research questions in a scientific manner, I conducted a series of fieldwork in rural China, as well as designed and executed extended reality assisted learning sessions and/or interventions with the rural residents. Three studies were developed as three chapters to showcase the main components of the entire research project. As a result, all studies suggest that leveraging extended reality technology as a means to reduce educational inequalities is not just a pipe dream. Extended reality technology has the potential to reduce educational inequalities in underdeveloped regions. The potential between extended reality technologies and educational activities that are adaptable to a variety of contemporary learning environments is also highlighted. Findings also implicate the importance of evidence-based development of extended reality solutions in education to address the diverse needs of learners in our society. However, limitations exist due to small sample sizes and pandemic restrictions, and future research should consider these factors. The final conclusion calls to embrace XR technology as a tool to create a more equitable educational landscape. Future research should focus on technology enhanced teaching and learning to ensure inclusivity, empowerment, and transformation in education.
APPROVED
Keywords: Reduce Inequalities; Extend Reality; Virtual Reality; Rural China; Quality Education